Prednosti, ovire, priložnosti in nevarnosti staranja v domačem okolju ter vloga sodobne tehnologije v tem procesu - Babnik, Katarina (Psihološka obzorja (Ljubljana), 2024)
Ageing in place is a modern policy solution used by developed countries to deal with ageing populations. The systematic review of the literature was guided by the following objective: Identify the strengths, barriers, opportunities and threats (SWOT) of ageing in place. Within this objective, we were also interested in the role of modern technology in ageing in place, i.e. the position that technology occupies in the evaluation scheme of the SWOT analysis. The literature review followed the PRISMA protocol (EBSCOhost, scholarly articles published between 2011 and 2021) and was conducted using the SWOT technique and thematic analysis to summarise the literature reviewed. The individual codes were grouped into basic themes and classified into a priori elements of SWOT analysis - organised themes: Strengths (attachment to home, home as a resource, identity, mental health, effective strategies to manage change), Barriers (individual correlates, vulnerable groups, interaction with the environment specific to the individual, ineffective strategies to manage change), Opportunities (institutional support for living in the home environment, specific interventions for older people, specific interventions in the home environment, modern technologies), Threats (inadequate infrastructure, socio-cultural context, limitations of modern technology). The review of the literature shows that the outcomes of ageing in place depend on individual, micro- and macro-ecological factors and the specific person-environment interaction. Modern technology can play a supportive role, but only as a technological tool, which is insufficient as it does not address all the psychosocial and practical needs of older people. Focusing exclusively on the use of assistive technologies can jeopardise ageing in place, especially for vulnerable groups.
Keywords: aging in place; literature review; pregled literature; staranje v domačem okolju; SWOT analiza; SWOT analysis; technology; tehnologija